Control of Spoken Vowel Acoustics and the Influence of Phonetic Context in Human Speech Sensorimotor Cortex - Bouchard, Kristofer E. (Society for Neuroscience, 2014)
Speech production requires the precise control of vocal tract movements to generate individual speech sounds (phonemes) which, in turn, are rapidly organized into complex sequences. Multiple productions of the same phoneme can exhibit substantial variability, some of which is inherent to control of the vocal tract and its biomechanics, and some of which reflects the contextual effects of surrounding phonemes (“coarticulation”). The role of the CNS in these aspects of speech motor control is not well understood. To address these issues, we recorded multielectrode cortical activity directly from human ventral sensory-motor cortex (vSMC) during the production of consonant-vowel syllables. We analyzed the relationship between the acoustic parameters of vowels (pitch and formants) and cortical activity on a single-trial level. We found that vSMC activity robustly predicted acoustic parameters across vowel categories (up to 80% of variance), as well as different renditions of the same vowel (up to 25% of variance). Furthermore, we observed significant contextual effects on vSMC representations of produced phonemes that suggest active control of coarticulation: vSMC representations for vowels were biased toward the representations of the preceding consonant, and conversely, representations for consonants were biased toward upcoming vowels. These results reveal that vSMC activity for phonemes are not invariant and provide insight into the cortical mechanisms of coarticulation.